Role of ruscogenin extracted from Radix Ophiopogon Japonicus in antagonizing 5-hydroxytryptamine and dopamine receptors through computational screening. - Suya Ma; Yongmei Liu (PLoS ONE, 2024)
The 5-hydroxytryptamine (5-HT) and dopamine (DA) receptors have emerged as significant targets for therapeutic intervention in psychiatric disorders. Currently, the efficacy of psychiatric drugs is limited by challenges in achieving desired outcomes, the occurrence of adverse effects, dependence, and withdrawal reactions. Consequently, there is a pressing need for the development of safe and effective therapeutic agents for psychiatric disorders. To explore the potential effects of natural product extracts as therapeutic agents for psychiatric disorders, 73 active ingredients from natural medicine extracts were screened to identify potential inhibitors of the serotonin 2A receptor (5-HT2AR) and dopamine D2 receptor (DRD2) using computerized virtual molecular docking. The most effective inhibitor of 5-HT2AR and DRD2 among these natural extracts was then evaluated for its drug-like properties using ADMET analysis, and its mechanisms of antagonism on DRD2 and 5-HT2AR were studied through molecular dynamics simulation. Risperidone was used as a positive control drug. The results showed that ruscogenin (RUS) was the most effective inhibitor of 5-HT2AR and DRD2, possessing favorable drug-like properties (most values of ADMET analysis were within the optimal range). When compared to risperidone, RUS exhibited more stable root mean square deviation (RMSD) plots, lower root mean square fluctuation (RMSF) values from residues 50 to 260, stronger hydrogen bonding interactions, higher compactness, a smaller solvent-accessible surface area (SASA) value, and lower binding free energy (-43.81 kcal/mol vs. -35.68 kcal/mol). RUS also demonstrated inhibitory effects on DRD2, as indicated by stable RMSD plots, low RMSF values from residues 50 to 250, strong hydrogen bonding interactions, high compactness, a small SASA value, and low binding free energy (-35.00 kcal/mol). Consequently, this research suggests that RUS, a natural pharmaceutical extract, is a promising candidate for further validation through clinical studies, representing a potential development of a therapeutic agent targeting psychiatric disorders.